Optimized removal of antibiotics over Cd0.5Zn0.5S/NiCo-LDH：Constructing a homojunctions-heterojunctions composite photocatalyst. Issue 6 (December 2022) - Dong, Wanyue; Cai, Tao; Wang, Longlu; Liu, Chuangwei; Chen, Hui; Li, Wenlu; Liu, Yutang; Xia, Xinnian
Abstract: A unique sheet-particle composite structure was constructed via loading NiCo-LDH as a co-catalyst onto the twinning Cd0.5 Zn0.5 S nanocrystals with inner homojunctions, which benefits to exposing more active sites. The photocatalytic performance of as-prepared catalysts was estimated by the degradation of norfloxacin (NOF) and tetracycline hydrochloride (TC-H) under visible light irradiation. The maximum removal rate of the selected CZS-NiCo8 towards TC-H and NOF over was about 88% and 73%, respectively. Compared with TC-H, the degradation of NOF is more affected by the adsorption of CZS-NiCo8. A series of photoelectric tests demonstrated that the surface type-Ⅱ heterojunctions were formed between Cd0.5 Zn0.5 S and NiCo-LDH, due to the enhanced light-harvesting property as well as the optimized photo-generated carrier transit. The radical trapping experiments and ESR results proved that h + and·O2 - were the main active radicals in the degradation of both TC-H and NOF. This work provided some ideas for the design of photocatalysts to remove antibiotics. Highlights: CZS-NiCo composite photocatalysts was synthesized by two-step hydrothermal method. CZS-NiCo8 exhibited excellent visible light degradation of TC-H and NOF. The twining structure of Cd0.5 Zn0.5 S induced zinc-blende/wurtzite homojunction into it. Type-Ⅱ heterojunctions were formed between NiCo-LDH and Cd0.5 Zn0.5 S. The degradation mechanism CZS-NiCo8 of was elucidated based on experimental results.